The current view of potentially inappropriate medications (PIMs) among older adults in Saudi Arabia: a systematic review - Alotaibi, Fawaz M. (Frontiers in Pharmacology, 2023)
Introduction: Potentially inappropriate medications PIMs are common among elderly population and becoming a global health issue. It has been associated with negative health consequences like preventable adverse drug reactions, hospitalization and mortality. Objectives: To investigate the most commonly potentially inappropriate medications in older adults in Saudi Arabia. Additionally, we aim to gain insights into the typical healthcare settings where healthcare providers offer services related to PIMs. Methods: This is a systematic review design using Preferred Reporting Items Systematic Reviews and Meta-Analysis (PRISMA) statement. PubMed and Google Scholar were used to search for the relevant studies using the following keywords (older adults, elderly, potentially inappropriate medications, inappropriate medications, PMIs, Saudi Arabia, Kingdom of Saudi Arabia) with no restrictions to the date of publications nor the study language. Results: Only 8 studies have met our inclusion and exclusion criteria, which was most of them were cross-sectional study design (n=6,75%) and all of them have been conducted in hospital-based settings. In addition, the prevalence of PIMs ranged from 19% to 80% depends on the site and administration of the study. We have found that proton pump inhibitors, non-steroidal anti-inflammatory drugs, aspirin, diuretics, gastrointestinal medications, and antidepressants were the most common reported PIMs in the included studies. Conclusion: The prevalence of PIMs among the elderly in Saudi Arabia is notably high ranged from 19% to 80%, underscoring the need for additional research to assess the existing practices within this vulnerable demographic across various healthcare settings.